Effects of dietary eucalyptol administration on antioxidant and inflammatory genes in common carp (Cyprinus carpio) exposed to ambient copper - Zohreh Fazelan (2020)
© 2020 Elsevier B.V. Copper sulfate is a common disinfectant in aquaculture that is used to remedy different diseases in fish. However, copper is toxic to fish, as well, causing oxidative stress and inflammation. Thus it is necessary to find methods to suppress adverse effects of copper sulfate treatment in fish. Eucalyptol was found to be antioxidant and anti-inflammatory agent; thus, it is of interest to find if eucalyptol treatment might suppress adverse effects of copper sulfate in fish. In this study, eucalyptol was examined to reduce oxidative stress and inflammation in common carp, Cyprinus carpio during exposure to copper sulfate. For this, the fish were fed diets supplemented with 0 (control), 0.5 and 1% eucalyptol for two weeks and exposed to ambient copper (0.25 mg/L as copper sulfate) for a further week. The fish were sampled before the copper exposure and 1 and 7 days after that. The results showed that both eucalyptol levels significantly increased superoxide dismutase (SOD; 1.4 and 1.5 folds), glutathione peroxidase (GPx; 1.4 and 1.6 folds) and catalase (CAT; 1.7 and 2.3 folds) activity, and decreased malondialdehyde levels (MDA; 1.7 and 1.4 folds) in the fish serum. Eucalyptol significantly up-regulated SOD (1.3 and 2 folds), GPx (1.7 and 2.3 folds) and CAT (1.2 and 1.6 folds), and down regulated tumor necrosis factor-α (TNFa; 1.6 and 1.9 folds), interleukin 1-beta (IL1b; 1.5 and 1.3 folds) and interleukin 8 (IL8; 1.1 and 1.3 folds) gene expressions in the fish kidney. On the other hand, copper exposure significantly decreased SOD (1.8 and 2.5 folds), GPx (1.6 and 1.4folds), and CAT (3 and 4 folds) activities in the fish serum, and their gene expressions in the fish kidney (2.5 and 1.9 folds, 1.5 and 1.7 folds, 2.5 and 3.1 folds, respectively). These fish showed significant elevation in serum MDA levels (2 and 2.9 folds), and kidney TNFa (1.7 and 1.8 folds), IL1b (1.5 and 1.7 folds) and IL8 (1.3 and 1.4 folds) gene expressions. Moreover, there were interaction effects of eucalyptol administration and copper exposure on serum CAT activity and MDA levels, as well as kidney CAT, IL1b, and IL8 gene expressions, so that, eucalyptol treatment significantly mitigated/delayed the changes in these parameters during the copper exposure. In conclusion, eucalyptol is capable to mitigate oxidative stress and inflammation in copper-exposed common carp, thus, it might be used before copper sulfate treatment in the farms. A two-week eucalyptol administration (1% of diet) is beneficial in reducing oxidative stress and inflammation in common carp that further exposed to copper sulfate.